2010
DOI: 10.1037/a0017513
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol demand, delayed reward discounting, and craving in relation to drinking and alcohol use disorders.

Abstract: A behavioral economic approach to alcohol use disorders (AUDs) emphasizes both individual and environmental determinants of alcohol use. The current study examined individual differences in alcohol demand (i.e., motivation for alcohol under escalating conditions of price) and delayed reward discounting (i.e., preference for immediate small rewards compared to delayed larger rewards) in 61Correspondence regarding this study should be addressed to James MacKillop, PhD, Department of Psychology, University of Geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
277
6
4

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(319 citation statements)
references
References 66 publications
(101 reference statements)
32
277
6
4
Order By: Relevance
“…Thus, in this case both punishment resistance and preferred level of drug intake are expected to contribute to the total shock selfadministered. Of note, Q 0 has been reported to be associated with alcohol-related problems and misuse (10,11,14) and nicotine dependence (12,13), and could be a clinically relevant measure of addiction severity. This is consistent with the view that Q 0 parameter is similar to hedonic set point (8), a concept thought to be important in addiction behavior (31,43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in this case both punishment resistance and preferred level of drug intake are expected to contribute to the total shock selfadministered. Of note, Q 0 has been reported to be associated with alcohol-related problems and misuse (10,11,14) and nicotine dependence (12,13), and could be a clinically relevant measure of addiction severity. This is consistent with the view that Q 0 parameter is similar to hedonic set point (8), a concept thought to be important in addiction behavior (31,43).…”
Section: Discussionmentioning
confidence: 99%
“…Economic demand is associated with measures of addiction in humans for several drugs, such as lifetime years of cocaine, heroin, marijuana, and benzodiazepine use (15); severity of alcohol dependence (10,11,14) and craving (16); as well as severity of nicotine dependence (12,13) and craving (17). A model of economic demand was recently validated in cocaine-dependent participants (9), providing the means for ready, direct comparison of animal and human studies of addiction treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that demand indices obtained from hypothetical purchase tasks have a high correspondence to other measures of abuse or dependence severity [5][6][7][8] , and other behavioral economic valuation procedures demonstrate high concordance between hypothetical and real rewards.…”
Section: Introductionmentioning
confidence: 99%
“…These indices can be grouped into two main measures of consumption, demand intensity and demand elasticity, which are associated with use level and dependence severity. [5][6][7][8] Demand intensity is the amount of the commodity consumed when available at a very low cost approaching free, and demand elasticity quantifies the degree to which the individual is willing to increase monetary or effort-based expenditures to maintain the same level of consumption as costs increase. Elasticity of demand has been shown to be a characteristic of the drug itself and independent of drug dose.…”
Section: Introductionmentioning
confidence: 99%